2006
DOI: 10.1093/toxsci/kfl069
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Elimination of Urinary Metabolites of Acrylamide in Humans

Abstract: Acrylamide (AM), used in the manufacture of polyacrylamide and grouting agents, is produced during the cooking of foods. Workplace exposure to AM can occur through the dermal and inhalation routes. The objective of this study was to define the kinetics of elimination of AM and its metabolites following oral and dermal administration. This is the second part of a study in which metabolites and hemoglobin adducts of AM were determined in people (Fennell et al., 2005, Toxicol. Sci. 85, 447-459). (1,2,3-(13)C(3))A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 42 publications
6
94
0
3
Order By: Relevance
“…With respect to the metabolic pattern of acrylamide and total dose recovery in the reference period, the toxicokinetic parameters were in accordance to the data from other human studies with acrylamide dosing (9)(10)(11)(12). For the disulfiram period, almost complete inhibition of CYP2E1 by the drug is expected.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…With respect to the metabolic pattern of acrylamide and total dose recovery in the reference period, the toxicokinetic parameters were in accordance to the data from other human studies with acrylamide dosing (9)(10)(11)(12). For the disulfiram period, almost complete inhibition of CYP2E1 by the drug is expected.…”
Section: Discussionsupporting
confidence: 83%
“…Acrylamide and glycidamide are conjugated to glutathione, which is the main pathway of acrylamide metabolism in both rodents and humans (10)(11)(12)(22)(23)(24). As products of this conjugation, the following mercapturic acid metabolites have been observed: N-acetyl-S-(2-carbamoylethyl)-cysteine (AAMA); N-acetyl-S-(2-carbamoylethyl)-cysteine-S -oxide; N -(R,S )-acetyl-S -(2-hydroxy-2-carbamoylethyl)-cysteine (GAMA); and Nacetyl-S -(1-carbamoyl-2-hydroxyethyl)-cysteine.…”
Section: Introductionmentioning
confidence: 99%
“…This modelling used all the male F344 rat data sets, including partition coefficients, blood and tissues, Hb adducts and urinary metabolites, previously fit by Young et al (2007) and Walker et al (2007). The human model was fit using the Hb adduct and urinary metabolite data from Fennell et al ( , 2006 (Sweeney et al, 2010) or Hb adduct measurements in rats and humans (Doerge et al, 2005a,b,c;Tareke et al, 2006). The human equivalent doses and reference values (i.e.…”
Section: Physiologically Based Pharmacokinetic (Pbpk) Modellingmentioning
confidence: 99%
“…Epoxidation of equal amounts of acrylamide to glycidamide is 2-4 times less in humans when compared to rodents [11][12][13]. Toxicokinetic studies in humans indicated that 60% of absorbed acrylamide is mostly eliminated in urine (86%) as GSH and just 4.4% of this incoming acrylamide was unchanged.…”
Section: Introductionmentioning
confidence: 99%